Antifungal activity of Stenotrophomonas maltophilia in Stomoxys calcitrans larvae - Ana Paula Rodrigues Moraes (Revista Brasileira de Parasitologia Veterinária, 2014)
The microbiota present inStomoxys calcitranslarvae may assist their survival in contaminated environments throughproduction of inhibitory substances. Bacteriological identification methods, the polymerase chain reaction (PCR)and scanning electron microscopy (SEM) were used to detect a bacterium naturally present in mucus and maceratedS. calcitranslarvae. The antifungal activity was determined based on the results from disk diffusion tests on an artificialsolid medium. The bacterium was identified asStenotrophomonas maltophiliaand presented antifungal activity againstBeauveria bassiana sensu latoisolates CG 138, CG 228 and ESALQ 986. This result suggests that the larval microbiotais a factor that can compromise the use ofB. bassianas.l.fungus for biological control ofS. calcitranslarvae.